A hybrid game theory and system dynamics model to determine optimal electricity generation mix. (October 2022) - Dehghan, Hamed; Nahavandi, Nasim; Chaharsooghi, S. Kamal; Zarei, Javad; Amin-Naseri, Mohammad Reza
Highlights: A hybrid game theory and system dynamics model of electricity supply is proposed. Optimal electricity generation mix is determined in different games. The share of green energy generation will reach about 28% by 2040 in Nash model. Water and gas use in Stackelberg-cooperation model decrease by 18.4 and 16.5%. Abstract: One criteria for the success in achieving sustainable development is to supply electricity by considering the diversity of generation technology. Also, the consumption of fossil fuels is considered as a major challenge for sustainable development. Relying heavily on fossil resources for electricity generation and the growing trend in emissions is one of the serious problems of developing countries. In this research, the sustainable growth of Iran's electricity industry in the short and long term time horizons is investigated using three game theory models in a system dynamic model. The competition, cooperation and profits of electricity suppliers as well as the government's role are modeled. Carbon dioxide emissions, water and natural gas consumption are also calculated. The results show the amount of carbon dioxide emissions, water and gas consumption in the Stackelberg and cooperation model decrease by 19.3%, 18.4% and 16.5%, respectively, compared to the continuation of the current trend.